The Clandestine Press in the Face of Fascist Violence in El Salvador: The Case of Prensa Comunista (1975-1978) - Baltazar Landeros, Edgar (2025)
In the context of the escalation of state violence in the 1970s, insurgent organizations with organs of propaganda and counterpropaganda emerged in El Salvador. This article situates itself within this process, analyzing the role of clandestine press in characterizing the military dictatorship using a predominant category: fascism. Through documentary sources from the insurgent clandestine press, the different uses and debates surrounding the category of "fascism" are examined. In particular, the content of Prensa Comunista, the clandestine publication of the Ejército Revolucionario del Pueblo (ERP) between 1975 and 1978, is analyzed.